Surveillance of Ixodes ricinus ticks (Acari: Ixodidae) in Iceland. - Alfredsson, M; Olafsson, E; Eydal, M; Unnsteinsdottir, E; Hansford, K; Wint, W; Alexander, N; Medlock, J (BioMed Central, 2017)
Background Ixodes ricinus is a three-host tick, a principal vector of Borrelia burgdorferi (s.l.) and one of the main vectors of tick-borne encephalitis (TBE) virus. Iceland is located in the North Atlantic Ocean with subpolar oceanic climate. During the past 3-4 decades, average temperature has increased, supporting more favourable conditions for ticks. Reports of I. ricinus have increased in recent years. If these ticks were able to establish in a changing climate, Iceland may face new threats posed by tick-borne diseases. Methods Active field surveillance by tick flagging was conducted at 111 sites around Iceland from August 2015 to September 2016. Longworth mammal traps were used to trap Apodemus sylvaticus in southwestern and southern Iceland. Surveillance on tick importation by migratory birds was conducted in southeastern Iceland, using bird nets and a Heligoland trap. Vulpes lagopus carcasses from all regions of the country were inspected for ticks. In addition, existing and new passive surveillance data from two institutes have been merged and are presented. Continental probability of presence models were produced. Boosted Regression Trees spatial modelling methods and its predictions were assessed against reported presence. Results By field sampling 26 questing I. ricinus ticks (7 males, 3 females and 16 nymphs) were collected from vegetation from three locations in southern and southeastern Iceland. Four ticks were found on migratory birds at their arrival in May 2016. A total of 52 A. sylvaticus were live-trapped but no ticks were found nor on 315 V. lagopus carcasses. Passive surveillance data collected since 1976, reports further 214 I. ricinus ticks from 202 records, with an increase of submissions in recent years. The continental probability of presence model correctly predicts approximately 75% of the recorded presences, but fails to predict a fairly specific category of recorded presence in areas where the records are probably opportunistic and not likely to lead to establishment. Conclusions To the best of our knowledge, this study represents the first finding of questing I. ricinus ticks in Iceland. The species could possibly be established locally in Iceland in low abundance, although no questing larvae have yet been detected to confirm established populations. Submitted tick records have increased recently, which may reflect an increase in exposure, or in interest in ticks. Furthermore, the amount of records on dogs, cats and humans indicate that ticks were acquired locally, presenting a local biting risk. Tick findings on migratory birds highlight a possible route of importation. Obtaining questing larvae is now a priority to confirm that I. ricinus populations are established in Iceland. Further surveys on wild mammals (e.g. Rangifer tarandus), livestock and migratory birds are recommended to better understand their role as potential hosts for I. ricinus.